Management of Disputed Inheritance Assets from the Perspective of Islamic Law and Positive Law - Makhbub Hidayatur Rohman; Eko Sariyekti; Zaenal Arifin (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2025)
The cancellation of the grant in kaloran through deliberation occurred, causing several plots of land to become disputed. The people involved chose to avoid settlement in court which they considered complicated and required more energy, so they chose to remain silent and ignore it, making the land dispute last for a long time. This creates a special incident where the land continues to be managed even though there has been no definite decision on the owner without causing conflict and remaining harmonious because the local community is known for its tolerance. So this study aims to determine the views of Islamic law and positive law on the management of disputed land in Kaloran District, Temanggung Regency. The research conducted applies a qualitative research method, with a sociological approach with primary data obtained through observation, and interviews, directly to related informants, while secondary data is obtained from books, journals, articles and laws. Dispute Land Management is permitted for several reasons, namely that there is no party who feels disadvantaged, there are no claims or lawsuits, and there are no articles violated by the land manager. Management does not cause conflict and disputes because the local community is a harmonious and tolerant area so that the incident is allowed with understanding because disputes over property are still considered embarrassing.